Odpowiedzi

2010-03-18T17:20:18+01:00
A)
2x+1=9-2x
2*2+1=9-2*2
4+1=9-4
5=5 tak

b)
3(2x-5)=1-4x
3(2*1½-5)=1-4*1½
3(3-5)=1-6
3*(-2)=-5
-6≠-5 nie

c)
4(y-6)-3y=2(y-9)
4(-6-6)-3*(-6)=2(-6-9)
4*(-12)+18=2*(-13)
-48+18=-26
-30≠-26 nie

8.
a)
4x-3=3x+5
4x-3x=5+3
x=8

b)
5x+2=7-3x
5x+3x=7-2
8x=5 /:8
x=5/8

c)
3(x-1)=0
3x-3=0
3x=3 /:3
x=1

d)
-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 /:(-6)
x=-5

e)
-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15 /:(-10)
x=1,5

f)
4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10 /:(-2)
x=-5
2 5 2
2010-03-18T17:29:09+01:00

6
a)2x+1=9-2x, 2
L= 2*2+1
P= 9-2*2
L= 5
P= 5
ODP. SPEŁNIA RÓWNANIE
b)
3(2x-5)=1-4x, 1½
L= 6x-30
P= 1-4x
L= 6*1,5 - 30
P= 1- 4*1,5
L= -25,5
P= 5
ODP. NIE SPEŁNIA RÓWNANIA.
c)
4(y-6)-3y=2(y-9), -6
4y - 24 - 3y = 2y - 18
L= 4*(-6) -24 - 3*(-6)
P= 2*(-6) - 18
L= -66
P= - 30
ODP. NIE SPEŁNIA RÓWNIANIA.
8.

a)
4x-3=3x+5
4x - 3x=5+3
x= 8

b)
5x+2=7-3x
5x+3x = 7-2
8x= 5 / : 8
x= 0.625
c)
3(x-1)=0
3x-3=0
3x=3 / : 3
x= 1

d)
-6(x+1)=24
-6x-6=24+6
-6x=30 / : (-6)
x= -5

e)
-7(x-2)=3x-1
-7x+14=3x-1
-7x+3x=-1-14
-4x= - 15 / : (-4)
x= 3 ¾
f)
4(x-1)=6(1+x)
4x-4= 6+6x
4x-6x=6+4
-2x= 10 / : (-2)
x= -5
:)
1 2 1